AMBITION IN WONKA MOVIE (2023): A PSYCHOLOGICAL PERSPECTIVE - Annisa Azhar; Syahara Dina Amalia (Elite Laboratory Jurusan Sastra Inggris Universitas Bangka Belitung, 2025)
This research article explores the theme of ambition in Wonka 2023 from a psychological perspective, focusing on the character Willy Wonka’s journey in establishing his own chocolate factory. The research uses qualitative methods, analyzing dialogues and scenes to understand how ambition affects Wonka and the characters around him. Based on Henry A. Murray’s theory of ambition, this research categorizes Willy Wonka’s ambition into three components: achievement, exhibition, and recognition. The research findings illustrate that Willy Wonka’s relentless pursuit of his goal significantly impacts the relationships and actions of his coworkers, highlighting the role of ambition in overcoming challenges and achieving success.